Protein and quality analyses of accessions from the USDA soybean germplasm collection for tofu production. (15th December 2016) - Meng, Shi; Chang, Sam; Gillen, Anne M.; Zhang, Yan
Highlights: Soybean accessions from USDA were screened for tofu production in U.S. Midsouth. A3 subunit was a suitable indicator predicting the firmness of filled tofu. Eight selected soybean lines made high quality tofu. Abstract: Food-grade soybeans with large seed size, uniformity, clear hilum and a high 11S/7S ratio are favoured by the food industry for making tofu. In order to search for soybean lines with desirable characteristics for making foods, 22 soybean lines were selected from the USDA-Soybean Germplasm Collection, were grown in Stoneville, MS for biochemical analysis and tofu texture and sensory quality tests. Eight lines were identified, from 22 lines harvested in 2014, to be suitable for tofu making, as judged by chemical composition and sensory quality of pressed tofu. In the filled tofu making and texture analysis study, the correlation between A3 subunit content and filled tofu firmness was significant (N = 22, r = 0.77, P < 0.001). The results indicated that the A3 subunit could be an indicator for predicting the firmness of tofu. The results provided important food quality information for the selection of soybean genotypes for improving food quality.